Pengaruh Kualitas Pelayanan, Kualitas Produk dan Harga terhadap Loyalitas Konsumen melalui Kepuasan Konsumen sebagai Variabel Intervening (Studi Kasus UMKM pada Soto Ayam Haji Karim) : (Studi Kasus UMKM pada Soto Ayam Haji Karim) - Purnomo, Nanto; Hidayatullah, Syarifudin (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2024)
This study aims to determine whether Service Quality, Product Quality, and Price affect consumer loyalty through consumer satisfaction as an intervening variable in Soto Ayam Haji Karim MSMEs and analyze the most dominant factors in influencing consumer loyalty and consumer satisfaction in the Soto Ayam Haji Karim Business. This study uses quantitative research methods with the population in this study being customers of Usaha Soto Ayam Haji Karim. The sample was taken as many as 100 respondents using the Non-Probability Sampling technique with a Purposive sampling approach, which is a sampling technique based on criteria, namely with the criteria of having bought Hajj Karim chicken disoto food 2 times. Data collection method using questionnaires or questionnaires. Data analysis techniques using SEM-PLS are processed with SmartPLS tool version 4.0. From the results of the study, it was found that Service Quality has a negative and significant effect on consumer loyalty, Product quality does not affect consumer loyalty, and price affects consumer loyalty, while Service Quality affects consumer loyalty through consumer satisfaction, Product quality does not affect consumer loyalty through consumer satisfaction, price does not affect consumer loyalty through consumer satisfaction. In the mediation test, it was found that the quality of service to consumer loyalty through customer satisfaction is called partial mediation, while the quality of service is called full mediation, and the price is called no mediation.